Generation of reactive oxygen species is the primary mode of action and cause of survivin suppression by sepantronium bromide (YM155). Issue 4 (15th February 2021) - Wani, Tasaduq Hussain; Chowdhury, Goutam; Chakrabarty, Anindita
Abstract : The anti-cancer drug YM155's primary mode of action is generation of reactive oxygen species, while survivin suppression and DNA damage are secondary effects. Abstract : Survivin is a lucrative broad-spectrum drug target for different cancer types, including triple negative breast cancer (TNBC). Sepantronium bromide (YM155) is the first of its class of survivin suppressants and was found to be quite effective in pre-clinical models of TNBC. However, in clinical trials when given in combination with docetaxel, YM55 failed to provide any added advantage. To understand if the clinical outcome is due to YM155 being ineffective or due to an inappropriate choice of combination, we need to elucidate its true mode of action. Hence, to explain the unexpected and unexplained observations pertaining to YM155 biology and its mode of action, we developed isogenic pairs of YM155-sensitive and -resistant TNBC cell lines and characterized them in detail by various biochemical assays. We found that YM155 generates reactive oxygen species (ROS) in the mitochondria in addition to the previously discovered redox cycling pathway. Both survivin suppression and DNA damage are secondary effects resulting from the ROS which contribute to the drug's cytotoxic effects on TNBC cells. Indeed, adaptation to both these pathways was important in conferring YM155 resistance. Finally, we uncovered a unique connection between the ROS and control of survivin expression involving a ROS/AKT/FoxO/survivin axis in TNBC cells. Together, by deciphering the true mode of action of YM155, we present a possible explanation for its poor clinical efficacy when used in combination with docetaxel. The results and conclusions presented here provide the information needed to effectively use YM155 in combination therapy.